Research on the Embedding Behavior of Ceramic Particles on the Surface of Epoxy Resin Anti-Skid Thin Layer of Pavement - Jiaquan Yuan; Gang Zhou; Chaoliang Fu; Wenhong Duan; Yifan Zhang; Haoyang Huang; Weihong Jiang; Li Xiong; Huimei Li; Xiaohua Yang; Chuanqiang Li (Buildings)
Colored polymer anti-skid thin layers are widely used on urban roads to enhance driving safety, improve road aesthetics, and mitigate the urban heat island effect. However, in thin layers constructed by the spreading method, the adhesion of cementitious material to the aggregate is often weak. This leads to early-stage spalling of surface aggregates, thereby reducing the anti-skid performance of the layer. To investigate the factors contributing to spalling, this study examines the embedding behavior of ceramic particles and assesses how the fluidity of the cementitious material and aggregate shape characteristics influence the embedding depth. Using a rotational viscosity test, it is concluded that a cementitious mix ratio of adhesive/powder filler/sand filler = 1:0.5:1 or 1:0.5:1.5 facilitates effective aggregate embedding. Testing the embedding depth of aggregates with the same particle size across different cementitious materials revealed that higher cementitious viscosity results in a reduced aggregate embedding depth. Geometric parameter data for aggregate particles were extensively collected using an image acquisition device, and quantitative analysis identified the shape characteristics influencing the embedding depth. A gray correlation analysis determined that the impact of the shape characteristics on embedding depth follows the order of roundness factor > prism factor > axial coefficient.